Current ZP3-based immunocontraceptive vaccine for free ranging wild pest - Lo, Sewn Cen; Allaudin, Zeenathul Nazariah; Abdul Rahman, Sheikh Omar; Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2011)
There is an overabundance of certain animal species that are considered as destructive and have reproductive control acts as a humane management of pest population. In particular, mammalian zona pellucida 3 (ZP3) has provoked a great interest as a potential antigen for immunocontraception. High levels of long-term infertility have been achieved in many species following ZP3-based immunization. This paper discusses the current updates on the ZP3-based immunocontraception for several major pest species of the world.